Design Of Real-Time Seismic Amplitude Measurement (RSAM) System Using Geophone as the Detection of Seismic Vibration - umi salamah; Apik Rusdiarna I.P; Qonitatul Hidayah; Aji Nur Rizki (LPPM Akademi Minyak dan Gas Balongan Indramayu, 2019)
Indonesia is one of the most volcanic countries in the world. The series of volcanoes extends from the islands of Sumatra, Java, Bali and Nusa Tenggara. From the islands in the Banda Sea to the northern part of Sulawesi Island is the longest volcanic region in the world. Indonesia has 129 active volcanoes, 70 of which are threatened and 500 are inactive. Since 1800, at least 600 recorded eruptions by 70 volcanoes in Indonesia. Therefore, Indonesia can be regarded as a country prone to disaster, especially the threat of disasters volcano. Observation, monitoring, recording, dissemination of information and warning signs of volcanic activity to be one focus in volcano disaster mitigation.One of the instrumentation used to monitor the volcanic activity of Mount Merapi is Real-time Seismic Amplitude Measurement (RSAM). RSAM is a system that provides a continuous measurement of the absolute average seismic amplitude of the number of seismic stations. RSAM occupies a strategic role in monitoring the seismic activity of volcano especially in times of crisis before the eruption. In this research, the RSAM system design using a geophone sensor to detect the seismic vibration. The frequency of the tests given in this study included 10 Hz, 30 Hz, and 50 Hz. The system that has been designed to build can detect frequencies well as evidenced by the greater the frequency of the test given the more the graph output of the output is produced. In addition, the magnitude produced is also getting bigger. At a frequency of 10 Hz, the resulting magnitude is 0.997, at 30 Hz the resulting magnitude is 1.559 while at 50 Hz the magnitude generated is 1.962 The RSAM system designed to build produces an amplitude that has a linear relationship to the magnitude of the vibration source provided.